OP0089 Abatacept is effective in experimental digestive and lung tissue fibrosis. (12th June 2018) - Boleto, G; Guignabert, C.; Pezet, S.; Cauvet, A.; Sadoine, J.; Tu, L.; Nicco, C.; Gobeaux, C.; Batteux, F.; Allanore, Y.; Avouac, J.
Abstract : Background: Cytotoxic T-lymphocyte associated molecule-4 (CTLA-4) is an immunoregulatory membrane receptor resulting in the down-regulation of T-cell responses. A previous report showed that abatacept (CTLA4-Ig) prevented and induced regression of inflammation-driven dermal fibrosis in two different mouse models of systemic sclerosis (SSc). 1 Objectives: We aimed to assess the effects of abatacept in two complementary mouse models reflecting digestive involvement, lung fibrosis and pulmonary hypertension (PH), mimicking severe SSc organ damage. Methods: Abatacept was given in the chronic graft-versus-host disease (cGvHD) mouse model, characterised by digestive involvement, and in the Fra-2 mouse model which is characterised by non-specific interstitial pneumonia and pulmonary vascular remodelling leading to PH. Mice were treated by intraperitoneal injections of abatacept (1 mg/mL in the cGvHD model for 6 weeks; 1 mg/mL or 10 mg/mL in the Fra-2 mouse model for 4 weeks) or human IgG1 (100 mg) used as a negative control. Results: In the cGvHD model, treatment of allogeneically mice with abatacept led to a significant reduction of alanine aminotransferase (24%, p=0.014) and aspartate aminotransferase levels (61%, p<0.001). Pathological analysis of colon revealed decreased inflammatory infiltrates and destruction of crypts in allogeneically mice receiving abatacept. When assessed by chest micro-CT imaging, Fra-2 mice treated with abatacept displayed a 12% decrease in lung density (10 mg/ml, p=0.037) as well as an increase in functional residual capacity as compared to IgG1-treated mice (16% for 1 mg/ml, p=0.001% and 14% for 10 mg/ml, p=0.005). Consistent with these results, abatacept 10 mg/L decreased histological fibrosis score (Ashcroft score) as well as hydroxyproline content by 79% (p=0.009) and 31% (p=0.044) respectively, as compared to IgG1-treated mice. Treatment with abatacept 10 mg/mL markedly reduced protein levels in the lesional lungs of Fra-2 mice of the fibrogenic markers MCP1 by 79% (p=0.043) and osteopontin by 87% (p=0.039). Levels of TGF-b were also reduced with abatacept (61% for 1 mg/mL, p=0.037% and 69% for 10 mg/mL, p=0.013). Further, abatacept decreased M1 and M2 macrophages infiltration as well as T-cell proliferation in the lesional lungs of Fra-2 mice. Upon treatment with abatacept a reduction of right ventricular systolic pressure (28.1±1.5 mmHg vs 36.0±5.1 mmHg, p=0.037 for 10 mg/mL) and right ventricular hypertrophy (0.29±0.01 vs 0.33±0.010, p=0.037 and 29±0.01% vs 0.33±0.01% for 10 mg/mL, p=0.037) was observed compared to IgG1-treated mice. Consistent with these findings, abatacept 10 mg/mL was associated with significant decrease in percent medial wall thickness and numbers of muscularized distal pulmonary arteries. Conclusions: We demonstrate that treatment with abatacept improves digestive involvement, prevents lung fibrosis and attenuates PH in SSc pre-clinical mice models. These findings suggest that abatacept might be an appealing therapeutic approach for severe internal organ involvement in SSc beyond its already demonstrated effects on skin fibrosis. Reference: [1] Ponsoye M, et al. Ann Rheum Dis2016Dec;75(12):2142–9. Disclosure of Interest: None declared